Fluorescence spectroscopy for tongue carcinoma detection: Study in an animal model - Kurachi, C.; Fontana, C. R.; Melo, C. A S; Rosa, L. E B [UNESP]; Bagnato, V. S. (SPIE, the international society for optics and photonics, 2005)
Fluorescence diagnosis of malignant lesions has been showed as an attractive optical technique due especially to its real-time response and a more objective and quantitative evaluation. Even though the oral cavity allows a direct examination many lesions are diagnosed when it is already in advanced stage, compromising the patient prognosis. In this study, the fluorescence spectroscopy was used to the detection of chemically induced carcinoma at the lateral border of the tongue in a hamster model. Two excitations wavelengths in visible region were applied: 442 and 532 nm. All the spectra results were analyzed comparing with the histopathological diagnosis. The better results were achieved with the 442 nm laser excitation. The spectra from carcinoma showed new emission bands and these were used to determined different ratios for a quantitative analysis. Using the 625-645 nm fluorescence range under 442 nm excitation (A3 coefficient) the percentage of false negative was of 9.1%, however the false positive percentage was of 18.5%. The 532 nm excitation provided a better normal tissue detection compared to 442 nm excitation. The ideal clinical condition is probably the use of multiple wavelengths excitation for a broader tissue fluorescence investigation.
Keywords: Diagnosis; Fluorescence; Spectroscopy; Tongue carcinoma; Alcohols; Biological organs; Histology; Metabolism; Nondestructive examination; Pathology; Tumors; Cancer detection; Fluorescene spectroscopy; Histopathological diagnosis